2021
DOI: 10.18805/ijare.a-5813
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Factors Influencing Seed Set in Oat

Abstract: Background: Oat is mostly neglected crop for hybrid development due to its floral structure which results in high damage rate during hybridisation. Due to the cumbersome in acquiring a sufficient number of hybrids and subsequent backcrosses are difficult that lead to lack of much inheritance studies in Oats. Methods: The procedure for crossing used was almost identical to that used by oat breeders which was conducted for 2 years viz., 2019-20 and 2020-21 at Forage Station, Punjab Agriculrural University, Ludhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Studies by some of the researchers showed that seed set as well as comparing the number of crossings produced in oats compared to others is low in percent. 7 The common cultivated oat is hexaploid constitutes of three genomes i.e. AACCDD.…”
Section: Floral Biology Of Oats and Its Progenitorsmentioning
confidence: 99%
“…Studies by some of the researchers showed that seed set as well as comparing the number of crossings produced in oats compared to others is low in percent. 7 The common cultivated oat is hexaploid constitutes of three genomes i.e. AACCDD.…”
Section: Floral Biology Of Oats and Its Progenitorsmentioning
confidence: 99%